Tiktok Shop Transactions in The Perspective of Islamic Business Ethics - Kamaruddin, Andi Martina; Ananda, Nur Indah Tri; Iqbal, Muhammad (KINERJA, 2024)
The purpose of this research is to determine whether TikTok Shop transactions at Jims Honey Samarinda align with Islamic business ethics. This study utilized a qualitative descriptive research method with data collection techniques including interviews, observations, and documentation. The participants in this study were the owner (seller) and three buyers at Jims Honey Samarinda, as well as Sharia experts. The results of the research indicate that the business ethics applied in the buying and selling transactions by Jims Honey Samarinda are in accordance with Islamic business ethics, including the principles of Unity, Balance, Will, Responsibility, and Truth (Virtue and Honesty).